STRATEGI KEAMANAN MARITIM INDONESIA DI KAWASAN SELAT MALAKA MELALUI KERJASAMA LITTORAL STATES (INDONESIA-MALAYSIA-SINGAPURA) PADA PEMERINTAHAN PRESIDEN JOKO WIDODO PERIODE I (2014-2019) - Yudha, Ishaq; Mahendra Wiswayana, Wishnu (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This article examines Indonesia's maritime security strategy in the Malacca Strait through cooperation with littoral states (Indonesia-Malaysia-Singapore) during President Joko Widodo's first term (2014-2019). Using a qualitative descriptive approach, this study analyzes Indonesia's implementation of maritime security based on Christian Bueger's Security Practice framework with five key components: Maritime Domain Awareness, Sea Operation, Law Enforcement, Coordination Among Multiple Actors, and Maritime Diplomacy and Capacity Building. The research reveals significant progress in Indonesia's maritime security capabilities, particularly through the establishment of Badan Keamanan Laut (Bakamla), improved maritime domain awareness, and increased sea operations. However, challenges remain, including technological limitations, budget constraints, fragmented coordination among national maritime agencies, and capability gaps compared to Malaysia and Singapore. Despite these challenges, Indonesia's Global Maritime Fulcrum vision provided strategic momentum for strengthening maritime security in the Malacca Strait, contributing to reduced maritime incidents in the region.